KERUGIAN NILAI BUDAYA ADAT SUKU ANAK DALAM PEMBANGUNAN PERKEBUNAN KELAPA SAWIT DI JAMBI - Walyoto, Sri (Journal of Islamic Economics Lariba, 2015)
Palm oil development in Jambi cause problems of society. This study was to estimate the economic loss of indigenous cultural communities palm oil development area. Economic concepts need to take into account cultural values consisting of value to direct and indirect use values which become elements of the construction costs. Direct use value from the perspective of the user community was estimated using TCM. Indirect use value is estimated using techniques CVM. The results obtained by the loss of indigenous cultural values of Rp4.517,4 million - Rp17.107,4 million. Area of research offers benefits to tourists and potential to become an eco-tourism destination nationally advanced culture to international efforts if it were made innovative improvements. This cultural value estimated using the lowest number based on population in Jambi Province alone, and do not take into account the population of other provinces in Indonesia as well as the population in the world. Increased public awareness of the importance of cultural and environmental preservation, cultural and environmental value benefits can go beyond the boundaries of a country.